Campus Link - Yazan Diab; Bassam Tuffaha (My University, 2024)
Our project is an easy and fun app and website designed for university students from all around the world. We’ve created a place where students can come together on one platform to make their studying and university life simpler. Our app includes a bunch of different universities, their courses, and even different majors. For each course, there’s a special page loaded with helpful things like e-books, videos, and notes. One of the best features of our app is the group project space. Here, students can work together on their assignments and chat in a special area, making teamwork smooth and enjoyable. We’ve also got a section for job offers. This part connects students with jobs that are a good fit for what they’re studying, which is great for finding part-time work or thinking about careers after university. Our app makes sure students don’t forget important stuff. It sends reminders about exams and due dates for assignments. Students can pick their courses for the semester, and the app will keep them updated with any new information or materials. But that’s not all. Our app has a really cool questions and posts page. Here, students can ask questions, and the questions they see are all about the courses they’ve chosen. This means they get to see stuff that’s really relevant to what they’re studying. Plus, if they want to, they can filter the questions to see only those from a specific course, college, or major. In short, our app is more than just about studying. It’s a whole package that helps with courses, group projects, job hunting, and staying organized. And the best part? It’s super easy to use and tailored to what students need.